Childhood discoid lupus erythematosus. A case treated with topical calcineurin inhibitors. - Sotiriou, E.; Apalla, Z.; Trigoni, A.; Giannopoulou, Ch.; Ioannides, D. (European Journal of Pediatric Dermatology, 2009)
Discoid lupus erythematosus (DLE) is the most common form of chronic cutaneous lupus erythematosus (LE). However, it is considered rare in childhood. Potent corticosteroids are frequently used in a topical setting and are presently considered a cornerstone in the treatment of childhood DLE. However, their prolonged use is related with severe adverse events. Present literature data argue for an efficacy of topical calcineurin inhibitors in acute and subacute LE, while chronic DLE lesions seem to be more resistant. The beneficial effect of topical pimecrolimus 1% in a 6-year-old girl with recent onset of facial DLE lesions suggests that calcineurin inhibitors could be an efficacious and safe treatment option for cutaneous lupus erythematosus of childhood.